Politics for a Pilgrim Church : A Thomistic Theory of Civic Virtue - Bushlack, Thomas J. (Grand Rapids, Michigan : William B. Eerdmans Publishing Company, 2015)
Church leaders and scholars have long wrestled with what should provide a guiding vision for Christian engagement in culture and politics. In this book Thomas Bushlack argues that a retrieval of Thomas Aquinas's understanding of civic virtue provides important resources for guiding this engagement today. Bushlack suggests that Aquinas's vision of the pilgrim church provides a fitting model for seeking the earthly common good of the political community, and he notes the features of a Thomistic account of justice and civic virtue that remain particularly salient for the twenty-first century. The book concludes with suggestions for cultivating a Christian rhetoric of the common good as an alternative to the predominant forms of discourse fostered within the culture wars that have been so divisive.
The theological challenge of political authority -- Civic virtue in Thomas Aquinas's account of justice -- A passion for justice -- Civic virtue and natural law -- Civic virtue and contemporary political philosophy -- Toward a constructive account of civic virtue and public rhetoric -- Politics for a pilgrim church.
Includes bibliographical references (pages 256-267) and indexes.
Keywords: Thomas, -- Aquinas, Saint, -- 1225?-1274.; Christianity and politics. -- Christian Ethics; Christianity and justice. -- Christian Ethics - Politics; Thomas Aquinas - Civic Virtues - Political Authority